Simulation of the three-dimensional flow in the human larynx - Céré, S. Préseault; Lormand, A.; Redekop, D.; Rouhi, G. (Canadian Acoustics, 2007)
Simulation of the three-dimensional flow in the human larynx is demonstrated. A three dimensional model was constructed to represent realistic structures from the trachea up to the epiglottis and the model was designed using approximations. The subglottic and supraglottic zones were constructed based on morphometric measurements. The results show that the process of simulation highlighted the interaction between the VFFAs and flow rate as the shape of the opening facilitates flow the glottal impedance should decrease. The flow rate and maximum velocity also increased with increasing the lung pressure. The recirculation in the ventricle when combined with the Conda effect shows that the effect could be a significant element on the behavior of the ventricular folds.